A systems-based approach to green criminology - Tourangeau, Wesley (Critical criminology, 2022)
Green criminology is grounded in debates regarding the ethics, legality, and reality of harms vis-à-vis the lives of non-human animals and the environment. The complex, uncertain, and ambiguous nature of these harms reveals the need for a more holistic approach: one that more firmly ties together social and ecological systems. In this paper, key aspects of systems thinking (e.g., leverage points) are outlined to illustrate the value of a systems-based approach. While not completely absent from green criminology literature, systems thinking offers a well-spring of underutilized ideas, concepts, theories, and frameworks that warrant further attention. A systems-based approach to green criminology is presented as a means to (re)imagine, (re)define, (re)examine, and respond to environmental harms.